Phylogenetic relationships of Malayan and Malagasy pygmy shrews of the genus suncus (soricomorpha: soricidae) inferred from mitochondrial cytochrome B gene sequences - Hashim, Rosli; Ruedi, M.; Omar, H.; Adamson, E.A.S.; Bhassu, S.; Goodman, S.M.; Soarimalala, V. (2011)
This study used a portion of the mitochondrial cytochrome b gene to investigate the phylogenetic relationships of Suncus pygmy shrews and to help clarify the taxonomic status of the Malayan pygmy shrew (S. malayanus) and the Malagasy pygmy shrew (S. madagascariensis). Phylogenetic reconstructions were performed using neighbour-joining and Bayesian analysis methods and revealed that S. malayanus is related to, but distinct from S. etruscus. The K2P-corrected genetic distance among the Malaysian taxon and other pygmy shrews for the cytochrome b gene was between 6.1 and 8.5%, supporting recognition that S. malayanus represents a distinct species from the geographically widespread S. etruscus species complex. A close (1.5% K2P distance) sister-group relationship was revealed between S. etruscus from Sri Lanka and S. madagascariensis from Madagascar, which has been considered an island endemic, and suggests that these animals are not specifically distinct. The Malagasy population of this shrew most probably was translocated to the island by human intervention, with the lineage originating from Southeast Asia or the Indian subcontinent.